Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential

Leaf morphology displays no detectable spatial organisation in the relict Quercus afares Pomel compared to the co-occurring parental species Q. canariensis Willd. and Q. suber L - Mhamdi, Samah; Brendel, Oliver; Montpied, Pierre; Ghouil-Amimi, Hanah; Hasnaoui, Ibrahim; Dreyer, Erwin (Annals of Forest Science, 2013)
•Context Oak species display a large within-species diversity combined with significant gene flow between species. Quercus afares Pomel is an endemic species that grows as a small relict population in Northern Tunisia, together with Quercus suber L. and Quercus canariensis Willd. It is considered to be a fixed hybrid between the two latter. •Aims We tested (1) whether this population of Q. afares is declining with respect to the neighbouring populations of the two other species and (2) whether the spatial distribution of leaf morphology is random among individuals within this small population of Q. afares or influenced by the neighbouring species. •Methods Spatial distribution and diameter at breast height were recorded in the population of Q. afares. We identified two perpendicular transects across the population reaching from areas dominated by Q. canariensis to areas dominated by Q. suber and defined 20 plots along each. Eleven traits were assessed on 10 leaves collected from the upper crown of trees from the three species. A multiple correspondence analysis and an ANOVA were used to test for within and between-species diversity in leaf morphology. •Results Q. afares individuals occurred at a low frequency among the two other species. Nevertheless, Q. afares showed no particular evidence of decline with respect to the two other species. Leaf traits displayed a large inter-specific variability with very little overlap between Q. afares and Q. suber and some between Q. afares and Q. canariensis. A high level of diversity was detected for these traits within Q. afares, but we were unable to unravel any spatial organisation of this diversity; in Q. afares, leaf traits varied independently of the presence of neighbouring Q. suber or Q. canariensis. •Conclusion Q. afares seems to be a fixed species with specific leaf traits that are independent of that of the species of the neighbouring trees. This population is not suffering a detectable trend towards decline except for the lack of any visible regeneration below any of the three species.
Keywords: Endemic oak species; Hybridization; leaf morphology; Mixed oak stands

Leaf traits variation during leaf expansion in Quercus ilex L. - Gratani, L; Bonito, A (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.
Keywords: leaf anatomy; leaf expansion; leaf morphology; net photosynthetic rate; Quercus ilex

Leaf traits variation during leaf expansion in Quercus ilex L. - GRATANI, L.; Bonito, A. (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.
Keywords: leaf anatomy; leaf expansion; leaf morphology; net photosynthetic rate; Quercus ilex

Ontogenetic changes in stomatal and biochemical limitations to photosynthesis of two co-occurring Mediterranean oaks differing in leaf life span - Juárez-López, Francisco José; Escudero, Alfonso; Mediavilla, Sonia (Tree Physiology, 2008)
A quantitative analysis was applied to the stomatal and biochemical limitations to light-saturated net photosynthesis under optimal field conditions in mature trees and seedlings of the co-occurring evergreen oak, Quercus ilex L., and the deciduous oak, Q. faginea Lam. Stomatal limitation to photosynthesis, maximal Rubisco activity and electron transport rate were determined from assimilation versus intercellular leaf carbon dioxide concentration response curves of leaves that were subsequently analyzed for nitrogen (N) concentration, mass per unit area, thickness and percent internal air space. In both species, seedlings had a lower leaf mass per unit area, thickness and leaf N concentration than mature trees. The root system of seedlings during their third year after planting was dominated by a taproot. A lower leaf N concentration of seedlings was associated with lower maximal Rubisco activity and electron transport rate and with assimilation rates similar to or lower than those of mature trees, despite the higher stomatal conductances and potential photosynthetic nitrogen-use efficiencies of seedlings. Consequently, stomatal limitation to photosynthesis increased with tree age in both species. In both seedlings and mature trees, a lower assimilation rate in Q. ilex than in Q. faginea was associated with lower stomatal conductance, N allocation to photosynthetic functions, maximal Rubisco activity and electron transport rate, and potential photosynthetic nitrogen-use efficiency but greater leaf thickness and leaf mass per unit area. Tree-age-related changes differed quantitatively between species, and the characteristics of the two species were more similar in seedlings than in mature trees. Despite higher stomatal conductances, seedlings are more N limited than adult trees, which contributes to lower biochemical efficiency.
10.1093/treephys/28.3.367
Keywords: A–ci response curves; biochemical capacity; leaf morphology; leaf N allocation; mature trees; Quercus faginea; Quercus ilex; seedlings; Stomatal conductance

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Díez, P. (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Diez, P (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate

The influence of summer and winter stress and water relationships on the distribution of Quercus ilex L. - Terradas, J; Savé, R (Plant Ecology, 1992)
Several aspects of plant-water relationships and canopy behaviour have been studied over several years in two experimental areas of Quercus ilex E. forests in the northeastern Iberian Peninsula. Water requirements, water status limits necessary for a positive carbon budget and the functional canopy be- haviour in the face of abiotic stress were evaluated, in order to determine which factors influence the geographical range of these forests. The results showed that holm oak has a conservative water use, a low cuticular transpiration, a high capacity for osmotic adjustement and xerophytic characteristics in leaf morphology and canopy arrange- ment. More than 440 mm of annual rainfall are required for these forests to persist. Summer drought and winter cold are thus important abiotic factors limiting the distribution of Quercus ilex. In both cases, drought stress is involved.
Keywords: canopy behaviour; Evapotranspiration; gaseous exchange; leaf morphology; plant-water